Retraction Note: The α7 nicotinic acetylcholine receptor agonist GTS-21 improves bacterial clearance in mice by restoring hyperoxia-compromised macrophage function - Ravikumar A. Sitapara; Daniel J. Antoine; Lokesh Sharma; Vivek S. Patel; Charles R. Ashby; Samir Gorasiya; Huan Yang; Michelle Zur; Lin L. Mantell (BMC, 2020)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s10020-020-00265-0